2022
DOI: 10.1083/jcb.202110073
|View full text |Cite
|
Sign up to set email alerts
|

Ribbon boosts ribosomal protein gene expression to coordinate organ form and function

Abstract: Cell growth is well defined for late (postembryonic) stages of development, but evidence for early (embryonic) cell growth during postmitotic morphogenesis is limited. Here, we report early cell growth as a key characteristic of tubulogenesis in the Drosophila embryonic salivary gland (SG) and trachea. A BTB/POZ domain nuclear factor, Ribbon (Rib), mediates this early cell growth. Rib binds the transcription start site of nearly every SG-expressed ribosomal protein gene (RPG) and is required for full expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…Perhaps having the abundant yolk and widely distributed hemocytes as the major sources of these growth-promoting hormones ensures their availability across all tissues in embryonic and early larval stages. Although the growth of embryonic cells has not, for the most part, been measured, we have discovered that both SG and tracheal cells double in volume during embryogenesis ( Loganathan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Perhaps having the abundant yolk and widely distributed hemocytes as the major sources of these growth-promoting hormones ensures their availability across all tissues in embryonic and early larval stages. Although the growth of embryonic cells has not, for the most part, been measured, we have discovered that both SG and tracheal cells double in volume during embryogenesis ( Loganathan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 92%
“…S3C,D ), likely provides for the corresponding increases in translation that support increased secretory load. Although increases in translation also support cellular growth, we suspect that the heightened enrichment of this process in the late SG more likely reflects its support of secretory function, as SG cell growth is continuous during embryonic development ( Loganathan et al, 2022 ). Our examination of SG TF expression reveals that, although we recovered fewer SG cells than expected at both stages, we easily detected TF transcripts that were only transiently expressed, some of which were also expressed in only a subset of SG cells.…”
Section: Discussionmentioning
confidence: 99%
“…A motif related to the BEAF-32B DNA binding consensus motif, CGATA (Hart et al, 1997; Zhao et al, 1995), represented around 15% of the occurrences of the top 10 motifs found in the Rib ChIP-seq peaks associated with the 494 genes (Loganathan et al, 2016). A more recent study found that Rib is associated with 73 of 84 ribosomal protein genes that are active in developing salivary glands and increases the expression of these genes, at least partially accounting for the requirement for Rib for salivary gland development (Loganathan et al, 2022). This work failed to detect sequence-specific DNA binding by Rib suggesting that it is recruited to DNA by other proteins.…”
Section: Resultsmentioning
confidence: 99%
“…BEAF could be one of several factors that helps recruit Rib to promoters. Other regulators of ribosomal protein gene expression (TRF2, M1BP, DREF) can co-immunoprecipitate Rib, making them additional candidates (Loganathan et al, 2022). If the SNP in the predicted PRE directly upstream of the rib promoter leads to rib activation in adult ovaries, Rib could replace the function of BEAF at genes such as those encoding ribosomal proteins to largely restore ovary function.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these data suggest that such increases in DNA content and translational capacity are likely necessary to support increased protein secretion. In fruit fly, salivary gland cells, which have high secretion demands, also exhibit similar features of up-regulation of ribosomal protein genes and nuclear division [78,79]. Therefore, enhanced translation capacity and larger cell size may be conserved features of cells needing to enhance secretion capacity.…”
Section: Discussionmentioning
confidence: 99%